2017
DOI: 10.1016/j.scitotenv.2017.04.088
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the inactivating factors and mechanisms exerted on MS2 coliphage in concentrated synthetic urine

Abstract: Volume reduction (condensation) is a key for the practical usage of human urine as a fertilizer because it enables the saving of storage space and the reduction of transportation cost. However, concentrated urine may carry infectious disease risks resulting from human pathogens frequently present in excreta, though the survival of pathogens in concentrated urine is not well understood. In this study, the inactivation of MS2 coliphage, a surrogate for single-stranded RNA human enteric viruses, in concentrated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…One potential mechanism that explains the relationship with coliphage reduction in primary processes and primary effluent ammonia is work by Oishi et al. () that demonstrated that ammonia inactivates the male‐specific coliphage MS2 through genomic damage. It is possible that enterococci may be more susceptible to ammonia than E. coli ; however, further work is needed to confirm these observations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential mechanism that explains the relationship with coliphage reduction in primary processes and primary effluent ammonia is work by Oishi et al. () that demonstrated that ammonia inactivates the male‐specific coliphage MS2 through genomic damage. It is possible that enterococci may be more susceptible to ammonia than E. coli ; however, further work is needed to confirm these observations.…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggests that WRRFs with higher influent ammonia concentrations may have higher removals of indicators, except for E. coli, in primary processes than WRRFs with lower influent concentrations of ammonia. One potential mechanism that explains the relationship with coliphage reduction in primary processes and primary effluent ammonia is work by Oishi et al (2017) Research Article that demonstrated that ammonia inactivates the male-specific coliphage MS2 through genomic damage. It is possible that enterococci may be more susceptible to ammonia than E. coli; however, further work is needed to confirm these observations.…”
Section: Indicator Reduction Through Primary Treatmentmentioning
confidence: 99%
“…48 Previous studies have simulated the fate of E. coli and MS2 in a feed solution using concentrated synthetic urine. 30,49 MS2 was inactivated more slowly than E. coli, and the time for a 5 log 10 inactivation was estimated as 4.8 months and 5 h for 10-folds concentrated non-hydrolyzed and hydrolyzed urine, respectively. Ammonia activity of 10-Environmental Science: Water Research & Technology Critical review fold concentrated urine was approximately 1000 mM.…”
Section: Urinementioning
confidence: 99%